2013
DOI: 10.1371/journal.pone.0059124
|View full text |Cite
|
Sign up to set email alerts
|

Incident Hip Fractures among Community Dwelling Persons with Alzheimer’s Disease in a Finnish Nationwide Register-Based Cohort

Abstract: BackgroundPrevious cohort studies have shown that persons with Alzheimer’s disease (AD) have a higher risk of hip fractures but recent data from large representative cohorts is scarce.MethodsWe investigated the association between AD and prevalent and incident hip fractures in an exposure-matched cohort study conducted in Finland 2002–2009 (the Medication and Alzheimer’s disease in 2005 study; MEDALZ-2005). The study population included all community-dwelling persons with verified AD diagnosis in Finland on De… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 36 publications
5
44
2
2
Order By: Relevance
“…The baseline risk of hip fracture also was higher among persons with AD compared with comparison persons. Previous studies have found that persons with AD have two times higher risk of hip fracture (Tolppanen et al, ), as well as the risk of falling seems to be two‐three times higher among persons with dementia (Allan et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…The baseline risk of hip fracture also was higher among persons with AD compared with comparison persons. Previous studies have found that persons with AD have two times higher risk of hip fracture (Tolppanen et al, ), as well as the risk of falling seems to be two‐three times higher among persons with dementia (Allan et al, ).…”
Section: Discussionmentioning
confidence: 95%
“…We also assessed the association between Ad and incident hip fracture 36. Although there was some evidence of effect modification by age and sex, Ad was consistently associated with a doubling of the risk of incident hip fracture.…”
Section: Resultsmentioning
confidence: 99%
“…Patients in the dementia cohort were more vulnerable to hip fracture than those in the comparison cohort. This result is consistent with a recent population‐based study in Finland (Tolppanen et al ., ). Contrary to a previous study that focused on Alzheimer‐type dementia, our study focused more on dementia patients than those with Alzheimer disease.…”
Section: Discussionmentioning
confidence: 97%
“…Contrary to a previous study that focused on Alzheimer‐type dementia, our study focused more on dementia patients than those with Alzheimer disease. Fewer case numbers were enrolled in our study cohort (3101 dementia patients in our study vs 56,180 patients with Alzheimer disease in the study by Tolppanen et al ) (Tolppanen et al ., ). To obtain an accurate dementia coding, only patients with more than five items of dementia coding were enrolled in our study.…”
Section: Discussionmentioning
confidence: 99%